Layer-by-layer films assembled from natural polymers for sustained release of neurotrophin. (11th September 2015) - Zhang, Zhiling; Li, Qianqi; Han, Lin; Zhong, Yinghui
Abstract: Cortical neural prostheses (CNPs) hold great promise for paralyzed patients by recording neural signals from the brain and translating them into movement commands. However, these electrodes normally fail to record neural signals weeks to months after implantation due to inflammation and neuronal loss around the implanted neural electrodes. Sustained local delivery of neurotrophins from biocompatible coatings on CNPs can potentially promote neuron survival and attract the nearby neurons to migrate toward the electrodes to increase neuron density at the electrode/brain interface, which is important for maintaining the recording quality and long-term performance of the implanted CNPs. However, sustained release of neurotrophins from biocompatible ultrathin coatings is very difficult to achieve. In this study, we investigated the potential of several biocompatible natural polyanions including heparin, dextran sulfate, and gelatin to form layer-by-layer (LbL) assembly with positively charged neurotrophin nerve growth factor (NGF) and its model protein lysozyme, and whether sustained release of NGF and lysozyme can be achieved from the nanoscale thin LbL coatings. We found that gelatin, which is less negatively charged than heparin and dextran sulfate, showed the highest efficacy in loading proteins into the LbL films because other interactions in addition to electrostatic interactions were involved in LbL assembly. Sustained release of NGF and lysozymes for approximately 2 weeks was achieved from the gelatin-based LbL coatings. Released NGF maintained the bioactivity to stimulate neurite outgrowth from PC12 cells. Gelatin is generally recognized as safe by the FDA. Thus, the biocompatible LbL coating developed in this study is highly promising to be used for implanted CNPs to improve their long-term performance in human patients.